Digitalizing High School Education: Exploring the Impact of Google Classroom and Virtual Classes - Iqbal, Faruk Alsayed (Journal Basic Science and Technology, 2024)
This research investigates the use of Google Classroom as a means of digitalizing high school education. The study delves into the impact of this digital platform on both students and edu-cators, focusing on the advantages, challenges, and broader implications of incorporating tech-nology into the classroom. Google Classroom offers several notable benefits, such as heightened student engagement, improved learning outcomes, and more efficient teacher-student commu-nication. It also encourages a shift in teaching methods, promoting personalized learning, col-laborative experiences, and resource efficiency. However, this research also underscores the sig-nificant challenges associated with digitalization, including issues related to equity, data privacy, digital distractions, and the potential drawbacks of overreliance on technology. The study con-cludes with recommendations for addressing these concerns, emphasizing the need for a bal-anced approach that leverages the advantages of digital tools while mitigating the challenges. Ultimately, digitalization holds great potential for enhancing high school education, but its suc-cessful implementation requires a thoughtful and comprehensive strategy that considers the evolving needs of students and educators in the digital age.Digitalization in Education; Google Classroom